Relationship As Pedagogy: Empowering Faculty To Support Student Mental Health In A Higher Education Setting - A Practical Theological Perspective - Anil Kumar Chillimuntha,; Eliah Srikakolli David, (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The increasing recognition of mental health issues among college students has necessitated a re-evaluation of pedagogical approaches in higher education. This research investigates the concept of "relationship as pedagogy" within the context of Christian higher education, specifically through the lens of Seventh-day Adventist (SDA) institutions. It explores how empowering faculty to build supportive, relational connections with students can enhance mental health support, align with the theological principles of the SDA Church, and contribute to a holistic educational experience. The study examines how faculty empowerment plays a pivotal role in implementing relational pedagogy. Faculty members are central to fostering a supportive educational environment, where relational connections can significantly impact students' mental health. Empowerment strategies include professional development focused on mental health awareness, relational teaching practices, and spiritual integration. By equipping faculty with the tools and knowledge to build trusting relationships, institutions can enhance their ability to address students' emotional and psychological needs effectively.